Epidemiological characteristics and interrupted time series analysis of mumps in Quzhou City, 2005–2023 - Canya Fu; Wenjie Xu; Wangfeng Zheng; Xiaoying Gong; Quanjun Fang; Zhiying Yin; Canjie Zheng (Human Vaccines & Immunotherapeutics)
To analyze epidemiological characteristics of mumps in different periods and explore the impact of different immunization strategies of mumps containing vaccine (MuCV) on the incidence of mumps in Quzhou. We collected reported cases of mumps in Quzhou from 2005 to 2023 for descriptive epidemiological analysis. Interrupted time series (ITS) analysis was used to assess changes in mumps incidence during the one-dose, two-dose, and the three-dose MuCV vaccination period. From 2005 to 2023, a total of 10,295 cases of mumps were reported. The average annual reported incidence rates during three period, were 57.5/100,000 (7015 cases), 14.8/100,000 (2590 cases), and 6/100,000 (690 cases), respectively. The male-to-female ratio reported cases was 1.58:1, and most cases were aged 5–9 years, accounting for 43.7%. ITS analysis showed an immediate decrease in monthly mumps incidence of 3.3951/100,000 after two-dose MuCV vaccination period (p = .022). However, the monthly mumps incidence only decreased by 0.1191/100,000 immediately after the implementation of the three doses of MMR vaccination (p = .411). The monthly incidence of mumps showed a slight increase of 0.0052/100,000 in the one-dose vaccination period, followed by a decrease of 0.0126/100,000 in the two-dose vaccination period, and a further decrease of 0.0004/100,000 in the three-dose MMR period (p > .05). This study shows that timely introduction of two doses of MuCV and ensuring high vaccination coverage are beneficial in controlling mumps epidemics. Currently, the key populations affected are children and adolescents, emphasizing the importance of addressing outbreaks within school epidemics.